2020
DOI: 10.1016/j.parkreldis.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Open-label titration of apomorphine sublingual film in patients with Parkinson's disease and “OFF” episodes

Abstract: The efficacy and safety of apomorphine sublingual film (APL-130277; APL) for the on-demand treatment of "OFF" episodes associated with Parkinson's disease (PD) was demonstrated in a double-blind trial. Herein we describe the ability of patients to receive effective and tolerable APL dose titration during the open-label titration phase. Methods: Adult patients with levodopa-responsive PD and "OFF" episodes were enrolled. In practically defined "OFF," patients were observed for a FULL "ON" after their usual morn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Although not specifically measured in this subgroup of patients, clinical and patient-reported findings from studies of apomorphine sublingual film help contextualize the PK findings of this report. In a post hoc analysis of the pivotal phase 3 trial, patients receiving apomorphine sublingual film experienced a ~ two-fold higher magnitude of motor response at 15 min postdose versus patients treated with CD/LD, the gold standard of therapy for PD [ 24 ]. In the pivotal trial, 37% of patients receiving apomorphine sublingual film noted improvement in their condition compared with 20% receiving placebo, as measured by the Patient Global Impression of Improvement scale; patients also reported improvement in their quality of life compared with placebo as measured by European Quality of Life–5 Dimensions instrument [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not specifically measured in this subgroup of patients, clinical and patient-reported findings from studies of apomorphine sublingual film help contextualize the PK findings of this report. In a post hoc analysis of the pivotal phase 3 trial, patients receiving apomorphine sublingual film experienced a ~ two-fold higher magnitude of motor response at 15 min postdose versus patients treated with CD/LD, the gold standard of therapy for PD [ 24 ]. In the pivotal trial, 37% of patients receiving apomorphine sublingual film noted improvement in their condition compared with 20% receiving placebo, as measured by the Patient Global Impression of Improvement scale; patients also reported improvement in their quality of life compared with placebo as measured by European Quality of Life–5 Dimensions instrument [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure-response modeling based on data from > 600 patients with PD enrolled across several apomorphine sublingual film studies demonstrated substantial interpatient variability in both plasma levels of apomorphine and changes in the MDS-UPDRS Part III scores, suggesting that a plasma concentration to achieve FULL “ON” will vary by patient [ 26 ]. In other clinical trials and in real-world use, at initiation of treatment, apomorphine sublingual film is titrated to the maximum efficacious and tolerated dose to provide a clinical benefit for the individual patient, thus overcoming some of the interpatient variability concerns observed in this small, single-dose study [ 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This formulation is conceived to systemically deliver the drug via absorption from the oral cavity mucosa, thus bypassing the extensive first-pass liver metabolism. Titration can be started at a 5–10 mg dose, which could be increased on subsequent days in 5–10 mg increments to a maximum of 40 mg until a full On-response is achieved [ 77 ]. The optimal dose is determined based on individual response, with a titration that can be performed at home without medical supervision, while anti-nausea therapy is not necessary.…”
Section: Oral Treatment Optionsmentioning
confidence: 99%
“…In addition, patient-assessed onset of ON within 60 min postdose was achieved on more days treated with apomorphine hydrochloride injection versus levodopa (93 % vs 54 %, respectively) [21] . In a post hoc analysis of the pivotal study of apomorphine sublingual film, the magnitude of motor response during open-label dose titration was ∼ 2-fold higher for sublingual film versus the first morning levodopa dose at 15 min postdose, and the peak response occurred earlier (45 vs 90 min) [60] . Further, patient-reported FULL ON was achieved by 72 % of patients treated with apomorphine sublingual film within 30 min postdose [60] .…”
Section: Use Of “On-demand” Treatments To Treat Off Episodesmentioning
confidence: 98%